Exploring the Impact of Emotional Eating in Children: A Narrative Review - Maria Mentzelou; Sousana K. Papadopoulou; Evmorfia Psara; Olga Alexatou; Theodosis Koimtsidis; Constantinos Giaginis (Pediatric Reports)
Background/Objectives: Emotional eating has been recognized as the tendency to eat in response to emotions, being recognized as a crucial risk factor for recurrent weight gain. Emotional eating has been interrelated with obesity/overweight, depression, anxiety, stress, and specific dietary habits at any stage of human life, negatively affecting human quality of life. The present study aims to summarize and explore the effects of emotional eating on children and how these effects may, in turn, influence their mental and physical health at the next stages of their lives. Methods: This is a narrative review of the presently existing clinical evidence concerning the impact of emotional eating in children. A comprehensive search of the most reliable online databases, e.g., PubMed, Scopus, Web of Science, and Google Scholar, was performed utilizing relevant keywords. Several inclusion and exclusion criteria were used to collect only cross-sectional, longitudinal, descriptive, and case–control surveys in children’s populations. Results: The current clinical evidence suggests that parental behavior may increase the risk of emotional eating in children. Several pieces of evidence also implied potential associations of emotional eating with overweight/obesity and mental disorders in children. Children’s dietary habits may also affect their risk of developing emotional eating. Conclusions: The prevalence of emotional eating is gradually increasing in the general population, and especially in children. Public strategies should be performed to educate parents to recognize potential emotional eating behaviors in their children and to adopt more healthy dietary habits for their children, even in the first months of their life. Educational programs should be organized in school communities to directly educate children on the benefits of healthy dietary patterns.